2012
DOI: 10.1017/s1049023x12001380
|View full text |Cite
|
Sign up to set email alerts
|

Community Assessment for Public Health Emergency Response (CASPER) One Year Following the Gulf Coast Oil Spill: Alabama and Mississippi, 2011

Abstract: Overall, mental health symptoms were higher in the three assessment areas compared to BRFSS reports, but lower than 2010 surveys. These results suggest that mental health services are still needed, particularly in households experiencing decreased income since the oil spill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…Our study reinforces other analyses of the DHOS of shorter duration. 30,31,38 For example, Hansel et al assessed recovery in 314 Gulf Coast residents in the first year following the DHOS (2010-2011) and again just after the second anniversary (2012). Using the same measure of depression we did, they found that depression scores between the 2 time periods remained largely unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reinforces other analyses of the DHOS of shorter duration. 30,31,38 For example, Hansel et al assessed recovery in 314 Gulf Coast residents in the first year following the DHOS (2010-2011) and again just after the second anniversary (2012). Using the same measure of depression we did, they found that depression scores between the 2 time periods remained largely unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Several factors have been proposed that may have acted as potential buffers to a psychological effect of the event in the general population; centrally, there were minimal spill-related injuries and mortality, disruptions to vital services, and long-term economic impacts. 16 However, there was substantial variability in post-spill mental health, with residents who experienced higher levels of physical exposure to oil during the oil spill or experiencing large financial impact at greater risk of adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Because the COR theory embraces so many aspects of individual, community, and socio-cultural entities, it has found considerable support after a wide variety of disasters, 20,2326 including the Deepwater Horizon Oil Spill. 13,27,28 …”
Section: Introductionmentioning
confidence: 99%